Clitoria ternatea L. petal bioactive compounds display antioxidant, antihemolytic and antihypertensive effects, inhibit α-amylase and α-glucosidase activities and reduce human LDL cholesterol and DNA induced oxidation. (February 2020) - Escher, Graziela Bragueto; Marques, Mariza Boscacci; do Carmo, Mariana Araújo Vieira; Azevedo, Luciana; Furtado, Marianna Miranda; Sant'Ana, Anderson S.; da Silva, Marcia Cristina; Genovese, Maria Inês; Wen, Mingchun; Zhang, Liang; Oh, Won Young; Shahidi, Fereidoon; et al.
Graphical abstract: Highlights: Bioactive compounds of Clitoria ternatea petals were extracted at 40 °C for 30 min. Aqueous extract has in vitro antihemolytic and antihyperglycemic effects. Lyophilized extract inhibited 61% of angiotensin-I-converting enzyme in vitro. Extracts showed an inhibitory effect of DNA strand scission and LDL cholesterol oxidation. Intracellular antioxidant activity with concentrations above 100 μg/mL of extract. Abstract: The purpose of this study was to use a statistical approach to optimise the experimental conditions regarding the extraction of bioactive compounds, and to analyse the in vitro functional properties of crude lyophilized extracts (CLE) and partially purified (PPE) extracts of Clitoria ternatea petals. The results showed that the factors of temperature and time influenced the extraction of phenolic compounds, antioxidant activity and the physicochemical parameters. Simultaneous optimisation showed that the same levels of bioactive compounds were extracted when using temperatures from 11.7 to 68.3 °C and times from 8.47 to 51.12 min. Principal component analysis revealed the experimental conditions that provided the extraction producing the highest level of phenolic content (40 °C/30 min). The CLE showed antimicrobial activity; protective effect against hemolysis of erythrocytes; inhibition of α-amylase, α-glucosidase and angiotensin-I-converting (ACE-I) enzymes; and inhibition of lipid peroxidation. The CLE and PPE demonstrated oxygen radical absorption capacity; inhibition of DNA strand scission; inhibition of LDL cholesterol oxidation; intracellular antioxidant activity against reactive oxygen species (>100 μg/mL); and no cytotoxicity (IC50, GI50 and LC50 > 900 μg/mL) against A549, HCT8 and IMR90 cell lines.